AGILITY PELAYANAN PUBLIK PADA MASA NEW NORMAL OLEH MALL PELAYANAN PUBLIK KOTA PEKANBARU - Dwi Seftia, Citra; Meiwanda, Geovani (Jurnal Ilmu Administrasi Negara, 2022)
Agility that is applied in public services during the new normal period at the Pekanbaru City Public Service Mall is aimed at the agility of the organization to respond quickly, in a timely manner. Agility is an organization’s ability to provide value to public satisfaction. This study aims to see whether there is agility in the Pekanbaru City Public Service Mall. The research method used is descriptive qualitative method using the theory of John Dowdy and Kirk Rieckhoff which consists of several indicators, namely strategy, structure, process and human resources. The result of this research is that the structural indicators have been running well. Meanwhile, in the indicators of the process and human resources, the implementation has not been maximized, there is still a lack of availability of human resources in the provision of services carried out by the Pekanbaru City Public Service Mall. Services in online form, namely the lack of understanding of employees about the implementation of online services, as well as the lack of education for the public in accessing online services. Meanwhile, for services in the new normal period, namely the limitation of labor which causes the services obtained by the community to be less than optimal. Researchers also provide suggestions that the importance of socializing to the community about how to access services online. Because, this service can be accessed by all people from the young to the old.